(untitled) (Journal of the College of Basic Education, 2023)
In the present work, Studying effect of concentration on the absorption and fluorescence spectra of eosin y in methanol in different concentration like 1x10-2, 0.5 x10-2,…. , 1x10-5 mol/liter, and afterward measure the absorptions spectra to this concentration like (abs.=521nm) for concentration (1x10-5 M) and (513 nm) for concentration (1x10-4 M) and also measure the fluorescence spectra like (582 nm) , (573 nm) ( 560 nm) (550nm), and also measure some photophysical parameters such as molar coefficient and oscillator strength and fluorescence coefficient , after that obtain increasing to the fluo. for different concentration and measure the abs. , by uv –vis Absorption and fluo. measure by using fluorometer spectropoto.